Cryptographic Authentication-Based Mechanism For Securing Secs/Gem Communications For Industry 4.0 Manufacturing - Laghari, Shams Ul Arfeen (2023)
This thesis proposes SECS/GEM Security Mechanism (SGSM) that offers authentication, integrity, and protection against cyber-attacks. The proposed mechanism is compared with the standard SECS/GEM, Secured SECS/GEM, and SECS/GEMsec mechanisms in terms of processing time, control overhead, and resilience against cyber-attacks. The SGSM exhibited promising results, indicating that it effectively enabled SECS/GEM devices to only communicate with authorized industrial equipment, maintained message integrity, discarded forged messages, and prevented attacks such as Denial-of-Service (DoS) attacks, Replay attacks, and False-Data-Injection-Attack (FDIA) attacks launched on SECS/GEM communications.